Application of innovative biotechnologies in the silk world breeding system - Khasanova Raykhon Bozarovna (THE INNOVATION ECONOMY, 2026)
Sericulture is one of the traditional and highly profitable branches of Uzbekistan’s agriculture. Silkworm egg production is the foundation of the entire industry, and the production of high-quality seeds (eggs) directly affects the yield of cocoons, quality indicators of cocoons, and the competitiveness of the finished product - silk fiber. In recent years, processes of modernization of the sericulture, introduction of new breeds and hybridization systems, and digitalization of technologies have been continuing. At the same time, there are a number of problems in the industry that need to be solved. This work highlights topical issues of the development of silkworm egg production and its economic efficiency. It analyzes the importance of producing high-quality silkworm eggs in the modern silk industry, the need to improve breeding and genetic development, and the introduction of innovative technologies in the incubation process.Optimal methods for organizing seed production for farms, efficient use of resources, disease prevention, and ways to increase seed productivity will also be considered. The research results show that a scientific approach, quality control, and the production of marketable products are important factors for achieving high profitability in silkworm egg production. It is noted that the development of seed production in the silk industry contributes to economic stability, increasing export potential, and ensuring the profitability of agricultural enterprises.